ETIKA KOMUNIKASI DALAM VEDA (TINJAUAN FENOMENOLOGI PADA ERA GLOBALISASI) - Untung Suhardi (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2018)
This research using triggered with the phenomenon that it is this day of the importance of the application of ethics in the life of , especially ethical in the vedas that exist in the life of religious social .This research using analysis deksriptif qualitative done with the approach phenomenology in of life at literature hindu .Research discussed about the history of communication in the vedas , ethics communication in the vedas and efforts the preservation of the implementation of the communication in the life of religious social . The result of this research showed that form of communication which limited only speak to your neighbor, but hindu give the findings for donations to civilization mankind that communication the most essential relationships are vertical with the almighty.Communication used in basic hindu thought this is what made the concept of the balance between spiritual life and a globe which is later, becomes the basis for behavior communicate in life in the present.In relation to the process communication veda is very long apply pattern interaction with your neighbor and its environment good horizontally with fellow human beings began of the family, the community and even to the national interest and state.Their effort to preserve ethics communication in the vedas formed by openness individual, the integration of all components hindu, capital intellectual as turning point in progress human resources, and sanction to local knowledge.